GENETIC DIVERSITY OF BIGEYE TUNA (Thunnus obesus) BASED ON rntDNA ANALYSIS WITH THE PCR-RFLP TECHNIQUE - Budi Nugraha; Mulyono Sumitro Baskoro; Anwar Bey Pane; Estu Nugroho (Indonesian Fisheries Research Journal, 2010)
The genetic diversity study of bigeye tuna in Indonesia from Indian Ocean has never been done. One of the analysis to obtain information on the genetic diversity is by using the PCR-RFLP technique.